80 Mbit/s Visible Light Communications Using Pre-Equalized White LED - Minh, H; O'Brien, D; Faulkner, G; Zeng, L; Lee, K; Jung, D; Oh, Y; IEEE (2008)
This paper reports an 80 Mbit/s OOK-NRZ Visible Light Communications experimental link using a single pre-equalized 45-MHz bandwidth white LED. © 2008 IEEE.